N16 'Same storm, different boat'… Exploring the impact of the COVID-19 pandemic on patients with Inflammatory Bowel Disease, with or without shielding: a qualitative study. (21st January 2022) - Kemp, K; Avery, P; Bryant, R; Cross, A; Danter, K; Kneebone, A; Morris, D; Walker, A; Whitley, L; Dibley, L
Abstract: Background: During the Covid-19 pandemic, patients with Inflammatory Bowel Disese (IBD) were advised about shielding based on clinical risk assessment. We explored experiences of IBD patients who did or did not shield during three UK lockdowns. Methods: Participants aged 18 years+ with a confirmed diagnosis of Crohn's disease, Ulcerative Colitis or IBD-Unclassified, who had shielded or not during any lockdown period were recruited from Crohn's and Colitis UK. Semi-structured online or phone interviews (captured February-May 2021) were audio-recorded, transcribed professionally, and analysed using thematic analysis. Results: Of 43 participants, 24 shielded; median age 38 years (19–63 years); 27 (62.7%) females; diagnosed with Crohn's Colitis (n=2), Crohn's disease (n=21), Ulcerative colitis (n=18) and IBD-Unclassified (n=2). Median disease duration 13 years (0.6–36 years). Participants were assessed as high (n-=10), moderate (n=23) and low (n=10) risk. Four main themes emerged: Vulnerability and Risk ; IBD Preparedness ; The Two Faces of Janus and Transitions . Vulnerability and Risk: The 'Clinically Extremely Vulnerable' label caused alarm, despite bringing benefits. Conflicting information caused confusion; some made their own decision about risk which did not always match official advice. Participants felt vulnerable to higher risk caused by others' behaviour. Some feared catching Covid. IBD Preparedness: Living with IBD prepared participants for shielding/social distancing. Many felt others now appreciated their usual world of periods of isolation and missing out on social events. Some realised the need to take their IBD more seriously. The Two Faces of Janus: The pandemic brought benefits and challenges to most participants. Working/studying from home often impacted positively on symptoms such as urgency and fatigue, as work and travel-related stresses eased. Loss of physical social contact with others was very distressing; many adopted new wellbeing activities to overcome social isolation. Few found the pandemic experience wholly positive. Transitions: the experience of lockdown changed over time, as did shielding patterns. The easing of restrictions (March-June 2021) left shielding and non-shielding participants feeling confused, since they felt the risk remained. Some participants continued to shield or be socially distant, often mistrusting others to behave responsibly. Conclusion: The pandemic had positive and negative effects for shielding and non-shielding participants alike. Adherence to Government shielding and/or social distancing guidelines was threatened by rising concerns about mental health and wellbeing. Any patient, regardless of official risk status, may need support to re-integrate socially.